2009
DOI: 10.1097/prs.0b013e3181a0720e
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Outcomes for Surgical Treatment of Patients with Chronic Migraine Headaches Caused by Occipital Neuralgia

Abstract: Neurolysis of the greater occipital nerve appears to provide safe, durable pain relief in the majority of selected patients with chronic headaches caused by occipital neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
134
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 40 publications
9
134
0
Order By: Relevance
“…The contribution of the lesser occipital nerve to migraine was validated by the research of Dr. Ivica Duicic who found that excision of the lesser occipital nerve relieved headaches. 45 However, the third occipital nerve does not have a significant clinical impact on the outcomes of migraine surgery. 46 Furthermore, occipital nerve and occipital artery intersections, as well as the third occipital nerve, were once considered to be the less common trigger sites.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the lesser occipital nerve to migraine was validated by the research of Dr. Ivica Duicic who found that excision of the lesser occipital nerve relieved headaches. 45 However, the third occipital nerve does not have a significant clinical impact on the outcomes of migraine surgery. 46 Furthermore, occipital nerve and occipital artery intersections, as well as the third occipital nerve, were once considered to be the less common trigger sites.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although results of published series have been encouraging, with an average 85% success rate, there are inevitably a subset of patients who fail decompressive surgery and continue to suffer from chronic headaches. 2 In some other neuralgic syndromes, peripheral nerve ablation has been used as a method of pain reduction, presumably by severing the connection of the central nervous system with the peripheral sensory distribution of the target nerve. 3 The purpose of this report is to examine our experience with performing occipital nerve excision (denervation) for relief of continued occipital headaches in those patients who have both failed maximal medical management and previously undergone occipital nerve decompression.…”
mentioning
confidence: 99%
“…However, as its applicability continues to be proven to diverse and exciting problems, 2,3 growth in the population of both peripheral nerve surgeons and patients is bound to continue, as evidenced by recent publications with nerve procedures numbering in the hundreds to thousands. 3,4 As the specialty grows in size, it is bound to mature in refinement of technique and indications, and expectations for patient outcomes will become more standardized. As has occurred with other fields (general surgery, orthopedics, etc.…”
Section: Discussionmentioning
confidence: 97%